Kinetics, subcellular localization, and contribution to parasite virulence of a Trypanosoma cruzi hybrid type A heme peroxidase (TcAPx-CcP) - Hugo, Martín (2017)
The Trypanosoma cruzi ascorbate peroxidase is, by sequence analysis, a hybrid type A member of class I heme peroxidases [TcAPx-cytochrome c peroxidase (CcP)], suggesting both ascorbate (Asc) and cytochrome c (Cc) peroxidase activity. Here, we show that the enzyme reacts fast with H2O2 (k = 2.9 × 107 M-1·s-1) and catalytically decomposes H2O2 using Cc as the reducing substrate with higher efficiency than Asc (kcat/Km = 2.1 × 105 versus 3.5 × 104 M-1·s-1, respectively). Visible-absorption spectra of purified recombinant TcAPx-CcP after H2O2 reaction denote the formation of a compound I-like product, characteristic of the generation of a tryptophanyl radical-cation (Trp233•+). Mutation of Trp233 to phenylalanine (W233F) completely abolishes the Cc-dependent peroxidase activity. In addition to Trp233•+, a Cys222-derived radical was identified by electron paramagnetic resonance spin trapping, immunospin trapping, and MS analysis after equimolar H2O2 addition, supporting an alternative electron transfer (ET) pathway from the heme. Molecular dynamics studies revealed that ET between Trp233 and Cys222 is possible and likely to participate in the catalytic cycle. Recognizing the ability of TcAPx-CcP to use alternative reducing substrates, we searched for its subcellular localization in the infective parasite stages (intracellular amastigotes and extracellular trypomastigotes). TcAPx-CcP was found closely associated with mitochondrial membranes and, most interestingly, with the outer leaflet of the plasma membrane, suggesting a role at the host-parasite interface. TcAPx-CcP overexpressers were significantly more infective to macrophages and cardiomyocytes, as well as in the mouse model of Chagas disease, supporting the involvement of TcAPx-CcP in pathogen virulence as part of the parasite antioxidant armamentarium.